Mystical Dimensions of Islam Thirty-fifth Anniversary Edition. - Schimmel, Annemarie, 1922-2003.; Ernst, Carl W., 1950- (Chapel Hill : The University of North Carolina Press, 2011)
As Carl Ernst makes clear in his new foreword to this thirty-fifth anniversary edition, Mystical Dimensions of Islam stands as a classic introduction to Sufism, the main form of Islamic mysticism, and one that will be hard to supersede. Its balanced historical treatment of the transnational phenomenon of Sufism, from its beginnings through the nineteenth century, the author's sensitivity and deep understanding of the subject, and her erudite examination of Sufism as reflected in Islamic poetry in Arabic, Persian, Turkish, Sindhi, Panjabi, and Pashto add up to a virtuoso demonstration of how Su.
The Arabic alphabet and note on transcription -- The Muslim year -- 1. What is Sufism? -- 2. Historical outlines of classical Sufism -- 3. The path -- 4. Man and his perfection -- 5. Sufi orders and fraternities -- 6. Theosophical Sufism -- 7. The rose and the nightingale : Persian and Turkish mystical poetry -- 8. Sufism in Indo-Pakistan -- 9. Epilogue -- Appendix 1. Letter symbolism in Sufi literature -- Appendix 2. The feminine element in Sufism.
Print version record.
Keywords: Sufism; Sufism; RELIGION / Islam / General; Electronic books